Hydrosphere objects screening control to detect emergency oil spill - Alexandr Martynovich Adam; Mikhail Valentinivich Begun; Alexandr Vladimirovich Dmitriev; Ekaterina Alekseevna Kupressova; Anna Mikhailovna Ledovskaya; Sergey Vladimirovich Romanenko; Oleg Gennadievich Savichev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
The current importance is caused by the need to improve the methodological and instrumental support, which corresponds to modern conditions and regional features, being one of the fundamental challenges before the environmental monitoring systems. Screening approach to solving this problem will become more advanced analytical tool condition monitoring of water bodies, especially those located in remote and difficult to access areas with high anthropogenic impact - oil production areas, allowing identifying quickly the occurrence of abnormal and emergency situations, leading to a negative impact on the environment, and taking more effective measures to eliminate them. The aim of the research is to prove water resources screening control methodology of remote oil production areas for detecting emergency oil spills on the example of Tomsk region. The research methods. It is proposed to use a screening approach to obtain information on the quality of natural waters, as well as timely detection of emergency situations occurred on the oil production and transportation facilities, leading to oil discharges to water bodies, together with the use of automated remote sensing methods and GIS technologies. For this purpose the environmental and geochemical conditions of water bodies in the accommodation areas of oil and gas companies were analyzed. The results and conclusions. The evaluation of the characteristic substances in the surface waters of the Ob River basin is carried out. The excess of the established water quality standards in most cases is caused by regional features of formation of their composition. The main difference of waste water composition of oil and gas complex of Siberia from the regional surface waters is expressed in rather larger content of Na+, Cl- ions, the sum of the main ions. The petroleum hydrocarbon content in produced waste water, sludge pits waters differs significantly from their concentrations in wetlands and its associated rivers and groundwater, which confirms the need to improve the effluents control and implementation of emergency early warning systems. It is necessary to use direct indicators (total petroleum hydrocarbons content by the fluorescence response) together with the indirect ones (chloride ion concentration, conductivity) as screening criteria in the accident detection methodology in oil production and transportation areas. It is caused by the peculiarities of their identification in natural aquatic environments. It was ascertained that the detection of anthropogenic oil pollution would be most reliable at concentrations from 1 mg/dm3 at a distance from the potential sources not more than 500 m.